2011
DOI: 10.4161/cc.10.3.14713
|View full text |Cite
|
Sign up to set email alerts
|

ATM-dependent ERK signaling via AKT in response to DNA double-strand breaks

Abstract: Ionizing radiation (IR) triggers many signaling pathways primarily originating from either damaged DNA or non-nuclear sources such as growth factor receptors. Thus, to study the DNA damage-induced signaling component alone by irradiation would be a challenge. To generate DNA double-strand breaks (DSBs) and minimize non-nuclear signaling, human cancer cells having bromodeoxyuridine (BrdU) - substituted DNA were treated with the photosensitizer Hoechst 33258 followed by long wavelength UV (UV-A) treatment (BrdU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 50 publications
5
57
0
Order By: Relevance
“…The induction of IL-8 signaling following CXCR1/CXCR2 interaction activates multiple signaling pathways and, as a consequence, triggers different effectors and downstream targets to promote angiogenic responses in ECs (29). PI3K is one of the principal effectors of IL-8, resulting in increased phosphorylation of its substrate serine/threonin kinase Akt (30), whose role in EC angiogenesis is well established (31). IL-8 signaling has also been shown to induce the activation of ERK1/2.…”
Section: Resultsmentioning
confidence: 99%
“…The induction of IL-8 signaling following CXCR1/CXCR2 interaction activates multiple signaling pathways and, as a consequence, triggers different effectors and downstream targets to promote angiogenic responses in ECs (29). PI3K is one of the principal effectors of IL-8, resulting in increased phosphorylation of its substrate serine/threonin kinase Akt (30), whose role in EC angiogenesis is well established (31). IL-8 signaling has also been shown to induce the activation of ERK1/2.…”
Section: Resultsmentioning
confidence: 99%
“…A very recent study suggested that DSB can influence ERK signaling via an ATM/AKT-dependent pathway, 48 and our data provide a mechanistic framework that helps to explain this phenomena. Furthermore, our finding that the MRE11 endonuclease activity is not required for DSB-induced pAKT-S473 suggests that this phosphorylation is not dependent on DSB resection.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 96%
“…The radiosensitivity of GBM cells can be affected by AKT and ERK signaling pathways through promoting the activation of the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) (28). ERK and AKT signaling pathways have positive effects on DSB repair in an ATM-dependent manner (29). It has been discovered that ATM indirectly induces AKT and ERK phosphorylation, and inhibiting the ATM kinase with an ATM-specific inhibitor was found to reduce the phosphorylation of AKT and ERK (30,31).…”
Section: Discussionmentioning
confidence: 99%